Report on the implementation of SB11-267: the Forest Health Act of 2011 - Jahnke, Jeff, author; Colorado State Forest Service, publisher (Colorado State University. Libraries, 2012)
Colorado's forested landscapes are essential to our well-being. Yet, these same landscapes are threatened by wildfires, insects and disease. Our ability to manage for these changes is limited by shrinking budgets, a declining forest products industry and volatile energy prices. However, these difficulties also present opportunities. Our current policy efforts should link forest health improvements and forest industry vitality to developing more efficient forest product manufacturing and encouraging renewable energy projects. To this end, the Colorado General Assembly passed Senate Bill 11-267: The Forest Health Act of 2011. The legislation created the Colorado Forest Biomass Use Work Group (Work Group) convened by the Colorado State Forest Service (CSFS). This report compiles the efforts of the Work Group. Specifically, this report addresses issues concerning forest energy by moving through the same process a forest energy project entrepreneur might follow during development. First, this report highlights problems with accessing and moving forest biomass material in Colorado. Next, it focuses on financing and planning issues. Finally, it details problems with current forest energy-related policies and utilization efforts.
Submitted by the Colorado State Forest Service; 1 January 2012; amended 20 February 2012.
Keywords: forest protection; Colorado; forest management; forests and forestry